PhD vs Pandemic: a qualitative study - Esperança, M. B.; Elbawab, R.; Costa, P. (VI International Forum on Management, 2022)
In pandemic times the notion of work-life balance has become more literal (Corbera et al., 2020). Our home became our full-time workplace (Corbera et al., 2020). Doctoral students have been affected by the pandemic (Decaux, 2021). Despite the research output importance few researchers have discussed the impact of the pandemic on the research and the researchers. Therefore, this research aims to assess the impact of the covid-19 on the PhD student’s research. How is the covid-19 impacting the PhD research? The main challenges and strategies to overcome the challenges were also assessed through a qualitative analysis. The data was collected in May 2021 through an online open-ended questionnaire and was analysed with MaxQDA. Our sample is composed of 27 PhD candidates based in Portugal, the majority are female (55%), between 35 and 44 years old (48%) and the majority is in the 1st and 2nd year (81%). Four negative outcomes were found - work-life balance, focus and motivation and time management. Regarding the response to these impacts, we found the following six strategies: acting on the well-being, disconnect from media, connect with others online, changing the work habits, the mindset, and the research planning. This study highlights the importance of good time management when our workplace is also our home. Few studies focus on the researcher rather than the research, the present study will be a basis to better prepare researchers to be able to continue to access all possible internal and external resources to produce good quality work.